Well‐defined, environment‐friendly synthesis of polypeptides based on phosgene‐free transformation of amino acids into urethane derivatives and their applications. Issue 3 (18th December 2019) - Endo, Takeshi; Sudo, Atsushi
Abstract: In this study, both naturally occurring and artificial amino acids were successfully transformed into the corresponding urethane derivatives using diphenyl carbonate. The urethanes thus prepared could be efficiently cyclized into amino acid N ‐carboxyanhydrides (NCAs) without the requirement of phosgene. In addition, the presence of primary amines converted the urethane derivatives into NCAs and initiated the ring‐opening polymerization of the in situ formed NCAs, allowing for the well‐defined synthesis of polypeptides. These polypeptides contained initiating ends functionalized by an amine‐derived residue and propagating ends bearing the reactive amino group. By precise control of the structures of the polypeptides, various polypeptide conjugates such as block copolymers and graft copolymers were successfully synthesized as designed, and their applications in antifouling coatings against proteins, drug delivery systems and biosensors were demonstrated. © 2019 Society of Chemical Industry Abstract : Amino acids were successfully transformed into the corresponding urethane derivatives using diphenyl carbonate (DPC). The urethanes thus prepared could be efficiently cyclized into amino acid N ‐carboxyanhydrides (NCAs) without the requirement of phosgene. In addition, the presence of primary amines converted the urethane derivatives into NCAs and initiated the ring‐opening polymerization of the in situ formed NCAs, allowing for the well‐defined synthesis of polypeptides.